Liquorice (glycyrrhiza glabra) hydroethanolic extracts effectively alleviate thioacetamide -induced hepatotoxicity and hematotoxicity in experimental rats through their antioxidant nature - Behairy, Alaa; Elkomy, Ashraf; Elsayed, Faten (International Journal of Pharmacology and Toxicology, 2020)
Background: Liquorice (Glycyrrhiza glabra) is a high valued plant and used in a lot of countries around the world. The liquorice (LQ) has a remarkable medicinal, nutritional and socio-economic value. Therefore this study was designed to clarify the protective effect of liquorice hydroethanolic extract against Thioacetamide (TAA) induced hepatotoxicity and hematotoxicity in rats.Materials and Methods: Seventy white Albino male rats were used in this study and after acclimatization rats were subjected to different treatments blood and tissue samples were collected after day 30 post administration, biochemical, antioxidant, hematological and histopathological examinations were utilized to investigate hepatoprotective activity of liquorice hydroethanolic extract.Results: TAA significant (P<0.05) increase the activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and hepatic malondialdehyde (MDA) compared to control group and silymarin(SL)treated group as stander, admin-istration of LQ extract restore the toxic effect of TAA , while TAA significant (P<0.05) decrease the levels of catalase(CAT) ,hepatic glutathione(GSH) hepatic superoxide dismutase (SOD) , total protein and albumin level compared to control group and silymarin(SL)treated group as stander, LQ extract ameliorate toxic effect of TAA. TAA induce hematotoxicity in rats by significant (P<0.05) decrease Hb content and RBCs, whereas WBCs count significantly (P<0.05) increased throughout the period of administration when compared to the rats in control group and silymarin(SL)treated group as stander,LQ administration protect against the hematotoxicity effect of TAA, TAA induce histopathological alteration in liver tissue by comparison with control group and silymarin(SL)treated group as stander, while LQ extract showing improvement in the histopathological lesion compared with toxic effect induced by TAA.Conclusions: The hepatotoxicity and hematotoxicity induced by TAA were ameliorated by hydroethanolic extract of LQ especially in double dose (200 mg/kg b.wt). This effect was attributed to free radical scavenging activity and potent antioxidant activity of its components (flavonoid, tannin and saponin).Â